NILAI BUDAYA DALAM CERITA RAKYAT ASAL USUL INDUSTRI KRETEK DI KUDUS - Sherin Himatussabrina; Anessa Nurhidayah; Ema Zulfiani; Fifit Fidyastuti; Mohammad Kanzunnudin (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
The kretek industry is one of the most important cultural and economic heritages in Indonesia, especially in the Kudus area, Central Java. Kretek cigarettes, a unique blend of tobacco and cloves, were first discovered as a medicinal herb by Haji Djamari in the late 19th century. This study aims to identify and analyze the cultural values contained in the folklore and review its relevance in children's literature education. The method used is qualitative descriptive with data collection techniques in the form of observing and taking notes on the folklore text, data obtained from the book Cerita Rakyat Pesisir Timur by Muhammad Kanzunudin. The results of the study show that this story has a strong educational function and is able to shape the local cultural identity of children in Kudus. The conclusion of this study is that the story of the Origin of the Kretek Industry has a strategic role as a medium for learning cultural values and needs to be integrated into children's literature learning to preserve local cultural heritage.